Differences between Chinese Mobile Payment and Foreign Mobile Payment - Yang Kangrui (SHS Web of Conferences)
Modern times have seen the emergence of creative payment methods thanks to technological advancements, with mobile payments becoming a major global influence. However, each country has a very different acceptance and trend for these digital transactions. The first section of this thorough analysis looks at how mobile payment systems have developed in China over the years and how they stand now in comparison to other nations. It explores the relationship between consumer behavior, regulatory settings, and technology improvements to understand the fundamental causes for the widespread use of mobile payments. The research then carefully examines the differences in mobile payment methods between China and other areas using Porter’s Diamond Model as a theoretical lens. It also looks at the difficulties foreign mobile payment apps have when tried to break into the Chinese market, such as the strong presence of well-established local rivals, the complexity of currency conversion rates, and the deeply ingrained user habits. The goal of this research is to present a comprehensive picture of the state of mobile payments and the many elements affecting their worldwide trend.